Miscommunication in pilot-controller interaction - Haryani Hamzah; Wong, Fook Fei (Penerbit Universiti Kebangsaan Malaysia, 2018)
English is the preferred language for communication in the aviation industry. Pilots and air traffic controllers of different nationalities and proficiency levels interact with each other using a specialized form of English termed aviation English that comprises of aviation phraseology and “plain English”. Here, miscommunication could have disastrous consequences. This paper presents the findings of a study that explored instances of miscommunication in the interaction between pilots and controllers. Miscommunication is defined as a lack of understanding (or misunderstanding), non-understanding or misinterpretation of messages in communication. The corpus consists of 30 hours of actual pilot-controller audio communication collected from the Malaysian airspace. Data were collected from three different frequencies (Alpha, Bravo and Charlie) representing different phases of the flight. They were analysed qualitatively using conversation analysis techniques. The study found that miscommunication in pilot-controller communication is due mainly to two main factors, procedural deviation and problematic instruction or request. The paper concludes by suggesting that pilots and controllers should adhere to standard phraseology and avoid code-switching from aviation phraseology to plain English except when it is inadequate for the situation. It also suggests that proper radio discipline should be maintained.